Dodatek k stritariani - Kavšek, Blaž (Slavistična revija, 2019)
In 1936, Anton Primožič donated his correspondence with Josip Stritar to Maribor's Study Library. Apart from the letters, it contains the transcript of three poems that Stritar carved into birch bark. A few days before the donation, one of them (the first one) was published by the newspaper Slovenec. Janko Glaser drew attention to these poems in 1939, but did not publish any of them. The editor of Stritar's Zbrana dela (Complete works), France Koblar, published the first and the third poem in the second volume (1953), but mentioned in a footnote that the second poem had been lost. In this article, I publish the second poem and consider how and why Koblar omitted it. Above all, I analyze the specifics of the treatment of the Primožič-Stritar correspondence in Slovenec and try to place it in the process of Stitar's (re)evaluation in the literary processing segment of the literary system.
Keywords: correspondence; empirical study of literature; empirična literarna veda; literarno zgodovinopisje; literary historiography; pisemska korespondenca; Primožič, Anton; Slovene literature; slovenska književnost; Stritar, Josip